Preference mapping of pineapples grown in Chiang Rai with different cultivars and cultivation methods for Thai consumers living in Chiang Rai - Sirimuangmoon, Chirat (Food and Applied Bioscience Journal, 2022)
Cultivar and cultivation method have been considered to have some effects on sensory characteristics and consumer acceptability in many types of fruits. These two factors were studied by focusing on two local cultivars of pineapples grown in Chiang Rai (Phu Lae and Nang Lae). Three different cultivation methods including cultivation with chemical fertilizers, cultivation with 100% organic fertilizer, and cultivation with natural condition were all applied. Commercial pineapples from both cultivars were also included. Eight pineapple samples in total were evaluated by 100 consumers by asking to rate their liking scores. The liking scores were then collected and analyzed with multivariate analysis in conjunction with cluster analysis, internal preference mapping, and regression analysis. Three clusters were all found after performing cluster analysis based on overall degree of liking, appearance liking, flavor liking, and texture liking. For overall degree of liking, consumers in the biggest cluster preferred Phu Lae pineapple in all cultivation methods and commercial Nang Lae pineapple, whereas consumers in a smaller group preferred commercial samples from both cultivars than other samples. Consumers in the other cluster preferred most of samples except commercial Phu Lae pineapple. For appearance liking, consumers in all three clusters liked the appearance of Phu Lae pineapple in all cultivation methods and commercial Nang Lae pineapple. One of 3 clusters was a group of consumers who liked the appearance of all samples except Phu Lae pineapple with organic cultivation. As for flavor liking, Nang Lae with organic and natural cultivation were the least liked by consumers. Commercial and chemical cultivation of Phu Lae pineapple were two samples that preferred by consumers in all three clusters. In case of texture liking, three samples including Phu Lae pineapple with chemical cultivation and commercial pineapple in both cultivars were preferred the most from consumers in all three clusters. Consumers in the main cluster showed their textural preference mainly on Phu Lae pineapple. Flavor was the main driver of liking for consumers in all 3 clusters. This result would be useful to understand effect of cultivar and cultivation methods on consumer acceptance toward pineapple.